Like, Share and… Prosecute? Social media as a mediating factor for prosecutorial discretion - Foo, Chester Wei Shen (Nanyang Technological University, 2020)
This paper analyses the relationship between prosecutors and social media by conducting interviews with legal practitioners from the state, Subject Matter Experts, and the public. We found the Attorney-General Chambers to be dismissive of social media, believing it to have weak validity and reliability, thus unable to represent public opinion. On the contrary, interviews with the general public and social media activists reveal that social media is useful for sharing information, to incite social change and as a reflection of public opinion, although they agree that there can be problems of representation and polarisation with social media. We argue for the importance of public opinion and suggest that social media has become a mediating factor in prosecutorial discretion and the deliberations on crime and punishment. We conclude that by exchanging information between the state and public, social media can become a powerful platform for civil discourse and informing prosecutorial discretion.